Reproductive Biology of Osteochilus hasselti C.Vfrom the Bunter Lake,Pangkalan Baru Village, Siak Hulu Sub District, Kampar Regency Riau Province - Dina Medina; Deni Efizon; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract Paweh fish (Osteochilus hasselti C.V) is type of fish commonly inhabit the Bunter lake of Pangkalan Baru Village. However, information on reproductive biology of the fish is rare. To understand the biological aspects of this fish, a study was conducted.The fish was sampled once at two weeks for three months period, from August to October 2019. Parameters measured were sex ratio, gonad maturity level, Gonad Somatic Index (GSI), fecundity and egg diameter. Result shown that there was 52 males and 36 females (sex ratio 1.6: 1).In each sampling time there were male and female fishes in 1st, 2nd, 3rd and 4th maturity level. The Gonad Somatic Index (GSI) of male is around 3.30%-9.64% and female is around 6.04%-16.40%. The average fecundity of the female was 10.497-29.540 eggs. Egg diameter was around 0.5-1 mm. This result indicated that paweh fish were total spawner. Keywords: Sex ratio, gonad maturity level, gonad somatic index, fecundity, total spawner